Unveiling multi-aspects behind students’ Arabic learning experience in creative writing - Arifa, Zakiyah; Fatim, Al Lastu Nurul; Sari, Risna Rianti; Zarkasyi, Ahmad Hidayatullah; Mulyanto, Dedi (International Journal of Evaluation and Research in Education (IJERE), 2025)
The dynamic of team-based project (TBP) in learning stimulates multi-aspects through learning activities and experiences. Due to its complexity, the learning model impacts some skills and aspects. This research aims to identify students’ experiences of learning Arabic creative writing in TBP: language, psychology, collaboration, and creativity, and to explain the contribution of those aspects to the learning process. To understand these experiences comprehensively, this research used mixed-method model: concurrent triangulation strategy using descriptive quantitative survey and qualitative case study. Closed and opened questionnaire instruments, interviews, and focused group discussion (FGD) with participants at two Islamic Universities were used as data collection methods to confirm them mutually. Then, data was analyzed using descriptive and reflective analysis. The results found that TBP positively impacted four aspects: vocabulary, grammatical structure, and writing skills improved as language aspects. The psychological aspect can increase criticism, motivation, and self-confidence. The collaborative aspect enhanced skills and talents by providing input, criticism, and suggestions. The creativity aspect is felt by students when generating ideas and imagination during the learning process and completing projects. Through learning Arabic creative writing using TBP, severalmulti-aspects can be developed. The psychological and collaborative aspects trigger and build language and creativity skills, and this contribution gives meaningful student experiences. These findings indicate that some students’ skills can be developed through student-centered learning by integrating TBP and Arabic writing learning, which has implications for improving 21st-century skills. Also, it can be developed more in Arabic language learning as a second/foreign language in Indonesia or other countries.